Evaluation of Coretax Revenue Through System Quality and Training of Tax Officials - Jaqueline Elizabeth Margaretha Tangkau; Pricilia Joice Pesak (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2026)
The purpose of this study is to provide empirical evidence on the use of coretax based on the modified Technology Acceptance Model (TAM). Employing a quantitative approach, this research surveyed a complete, saturated sample of 122 tax officials at the regional office of DGT Suluttenggomalut. The data was analyzed using PLS-SEM. The research findings reveal that perceived usefulness significantly mediates the impact of system quality and training on coretax utilization. Interestingly, system quality and training exhibit absolutely no direct influence on actual system usage. Furthermore, perceived ease of use is entirely unable to serve as a mediating variable between these factors and coretax utilization. Ultimately, this study introduces a novel perspective to existing TAM literature, demonstrating that within mandatory information systems, perceived usefulness remains the absolute key factor compelling individuals to willingly adopt and use the technological platform.